THE IMPORTANCE OF KNOWLEDGE IN ISLAMIC PERSPECTIVE - Dewi Suriyani Djamdjuri; Qarira Muti Kamila (Jurnal Intelek Insan Cendikia, 2025)
The article examines the significant importance of knowledge (Ilm) in Islam, emphasizing its critical role in personal and societal growth. Drawing on Qur'anic texts and Hadith, it emphasizes the Islamic need to pursue knowledge in both religious and general areas. Using a literature review approach, the discussion focuses on the ethical implications of learning, the relationship between knowledge and faith, and Muslim intellectuals' historical contributions to subjects such as physics, philosophy, and medicine. Islam promotes a comprehensive approach to education that encourages personal growth, ethical behavior, and society improvement by combining spiritual and intellectual activities. Islamic education, which integrates both spiritual and physical knowledge, is essential in forming moral and spiritual character. It places a heavy emphasis on lifelong learning and encourages people to cultivate a solid ethical basis and sense of moral responsibility. The goal is to create well-rounded, knowledgeable people who also exhibit characteristics like discipline, respect, and morality. By ensuring that intellectual development is balanced with moral and spiritual responsibilities, this all-encompassing approach equips people to meet societal challenges and make constructive contributions to their communities.